Chemical targeting of NEET proteins reveals their function in mitochondrial morphodynamics - Molino, Diana; Pila-Castellanos, Irene; Marjault, Henri-Baptiste; Dias Amoedo, Nivea; Kopp, Katja; Rochin, Leila; Karmi, Ola; Sohn, Yang-Sung; Lines, Laetitia; Hamaï, Ahmed; Joly, Stéphane; Radreau, Pauline; et al. (EMBO reports, 2020)
Abstract Several human pathologies including neurological, cardiac, infectious, cancerous, and metabolic diseases have been associated with altered mitochondria morphodynamics. Here, we identify a small organic molecule, which we named Mito-C. Mito-C is targeted to mitochondria and rapidly provokes mitochondrial network fragmentation. Biochemical analyses reveal that Mito-C is a member of a new class of heterocyclic compounds that target the NEET protein family, previously reported to regulate mitochondrial iron and ROS homeostasis. One of the NEET proteins, NAF-1, is identified as an important regulator of mitochondria morphodynamics that facilitates recruitment of DRP1 to the ER?mitochondria interface. Consistent with the observation that certain viruses modulate mitochondrial morphogenesis as a necessary part of their replication cycle, Mito-C counteracts dengue virus-induced mitochondrial network hyperfusion and represses viral replication. The newly identified chemical class including Mito-C is of therapeutic relevance for pathologies where altered mitochondria dynamics is part of disease etiology and NEET proteins are highlighted as important therapeutic targets in anti-viral research.